If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13c + 7 + -9c + 12c = 0 Reorder the terms: 7 + -13c + -9c + 12c = 0 Combine like terms: -13c + -9c = -22c 7 + -22c + 12c = 0 Combine like terms: -22c + 12c = -10c 7 + -10c = 0 Solving 7 + -10c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -10c = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -10c = 0 + -7 -10c = 0 + -7 Combine like terms: 0 + -7 = -7 -10c = -7 Divide each side by '-10'. c = 0.7 Simplifying c = 0.7
| x*3/5+x*3/4 | | |7-2x|=3 | | (6a^2+3a)/3a | | 27-2m=20 | | 5x+19=14x-64 | | -(3+3.5)= | | 40=-5(4-4p) | | 8p-3=5 | | 4(x+2)-5(x-7)=10x-5x-5 | | 6-5x-4x=6-2x | | (-12)-14= | | -6v-5v=0 | | 5/4*28=4/5n*5/4 | | (5x+24)=24 | | (2x+18)=24 | | 4x+-9x+22=3x+50 | | -4=7/35x | | 2/3+f/3=16 | | (3x+6)=24 | | 8(-10+b)=-8 | | -25-5m=-7(4m-3) | | -40x^3+64x^2-18x-20=0 | | a-(-11)=26 | | 11.6+3x=-16.8 | | 9t+1/4=t+6/8+t-4/8 | | (2x)/(x^2-1) | | 4(x+1)+4x=5x-14 | | 3u+(u+8/2)=10 | | 2(x+8)=4x-2 | | 8+16-1=9 | | -45=3(2x-3) | | 9x+9+9x= |